Boosting the anode performance of microbial fuel cells with a bacteria-derived biological iron oxide/carbon nanocomposite catalyst. (April 2021) - Yang, Qinzheng; Yang, Siqi; Liu, Guangli; Zhou, Bin; Yu, Xiaodi; Yin, Yanshun; Yang, Jing; Zhao, Huazhang
Abstract: Modifying the electrodes of microbial fuel cells (MFCs) with iron oxides can improve the bacterial attachment performances and electrocatalytic activities for energy conversion, which is of significance in the fabrication of MFCs. However, the conventional modification methods usually result in the aggregation of iron sites, producing the electrodes of poor qualities. Herein, we report a novel method for the modification of electrochemical electrodes to boost the anode performance of MFC. The Shewanella precursor adhered on carbon felt electrode was directly carbonized to form a bacteria-derived biological iron oxide/carbon (Bio-FeOx/C) nanocomposite catalyst. The large spatial separation between the bacteria, as well as those between the iron containing proteins in the bacteria, deliver a highly dispersed Bio-FeOx/C nanocomposite with good electrocatalytic activities. The excellent microbial attachment performance and electron transfer rate of the Bio-FeOx/C modified electrode significantly promote the transfer of produced electrons between bacteria and electrode. Accordingly, the MFC with the Bio-FeOx/C electrode exhibits the maximum power density of 797.0 mW m −2, much higher than that obtained with the conventional carbon felt anode (226.1 mW m −2 ). Our works have paved a new avenue to the conversion of the natural bacterial precursors into active iron oxide nanoparticles as the anode catalyst of MFCs. The high catalytic activity of the prepared Bio-FeOx endows it great application potentials in the construction of high-performance electrodes. Highlights: The anode catalyst was prepared by carbonization of iron containing bacteria. A biologically derived iron oxide is dispersed in nitrogen-doped graphitic carbon. The modified anode significantly increased the power densities of MFCs.